Comparisons of the price received per sack by soybean producers in Brazil (Research, Society and Development, 2020)
The soybean crop is one of the most important crops in Brazilian and worldwide agribusiness.Given the importance of soy culture for agribusiness, the objective of this study was toanalyze and compare prices for the sack of soy received by producers in differentmunicipalities, states and regions in Brazil. In this study, an exploratory research was carriedout with descriptive data of the quantitative type provided by the National Supply Company.Statistical data were analyzed between the months of May 2019 to April 2020 of the soybeancrop in one hundred and two municipalities distributed in fifteen states. The southern regionof Brazil has the highest appreciation of the soybean sack at the national level. In the Midwestregion, the Federal District, and the municipality of Rondonópolis, inMato Grosso, in theNortheast, the state of Maranhão, and Mata Roma/MA, in the North, the state of Pará, and themunicipalities of Dom Eliseu/PA and Paragominas/PA, in the Southeast region, the state ofMinas Gerais, and Uberaba/MG and Uberlândia/MG and inthe South region, the state of RioGrande do Sul, and Pelotas/RS, Vacaria/RS and Bagé/RS presented the greater appreciationof the soybean sack among the states at the regional and state levels. The factors that affectthe price received for the sack of soybeans by the producers are the significant distancesbetween the production areas of the commodity and the ports, the climatic adversities and the changes/variations in the global balance of supply and demand mediated by the ChicagoStock Exchange.